To find the equation of the exponential function represented by the table, we can start by assuming that the function is of the form y = a * b^x, where a and b are constants.
Using the given table, we can substitute the given x and y values into the equation:
For x = 0, y = 0.02:
0.02 = a * b^0
0.02 = a * 1
a = 0.02
For x = 1, y = 0.06:
0.06 = 0.02 * b^1
3 = b
So the equation becomes y = 0.02 * 3^x.
Find the equation of the exponential function represented by the table below:
x y
0, 0.02
1, 0.06
2, 0.18
3, 0.54
1 answer